Synthesis and properties of material based on organic silica and zeolite mordenite - Huong, Nguyen Thi; Son, Le Thanh; Con, Tran Hong (Vietnam Journal of Chemistry, 2015)
The materials based on organic silica and zeolite mordenite were synthesized from self-assembly of polymethylhydrosiloxane, tetraethoxysilane and zeolite mordenite using sodium hydroxide as catalyst. The structure characteristic and the porosity of the resultant mesoporous material were studied by SEM, XRD and the nitrogen adsorption isotherm techniques. Chemical bondings were characterized by using Fourier transform infrared spectroscopy. Results indicate that the obtained materials exhibit the large surface area and porosity.